Model Penyelesaian Masalah Keputusan Pembelian: Evaluasi Indikator Digital Marketing dan Online Customer Review di Toko Jangkar Kota Serang - Muhamad Suhaemi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is related to how the influence of digital marketing on purchasing decisions at the Toko Jangkar Kota Serang. The purpose of this study was to examine the effect of digital marketing on purchasing decisions partially, the effect of online customer reviews on purchasing decisions partially, the effect of digital marketing and online customer reviews on purchasing decisions simultaneously at the Toko Jangkar Kota Serang. Respondents in this study were 130 people. The type of sample in this study is non-probability with purposive sampling technique. The data collection method used is to use questionnaires and explained by quantitative methods. The results of this study indicate that digital marketing has a positive and significant effect on purchasing decisions, then online customer reviews also have a positive and significant effect on purchasing decisions. The two independent variables in this study are also empirically supported and simultaneously influence the dependent variable.